Pulmonary infections in the hematopoietic cell transplant patient. Issue 2 (April 2020) - Ford, Emily S.; Crothers, Kristina; Cheng, Guang-Shing
Abstract : Purpose of review: Despite progress in the management of pulmonary infections in the hematopoietic cell transplant (HCT) population, substantial diagnostic, and therapeutic uncertainty remains. Recent findings: A growing HCT population reflects more transplants and improved long-term survival. We continue to learn about the epidemiologic and prognostic significance of posttransplant pulmonary infections. Mold-active triazoles have removed invasive fungal pneumonia as a barrier to transplant eligibility. Ibrutinib and respiratory viruses are newly recognized risk factors for invasive fungal disease. Prophylaxis has elevated concerns of resistance in invasive fungal species and late onset Cytomegalovirus . The impact of human herpesviruses, community-associated respiratory viruses, and the microbiome is increasingly appreciated. Multiple antiviral therapies are currently in clinical trials and novel molecular diagnostics may improve the performance of bronchoscopy for infectious causes. Summary: Fungal and viral pneumonias remain an important cause of morbidity and mortality in the HCT population. Despite our increased understanding of the epidemiology and outcomes of species-specific diagnoses, the utility of invasive diagnostic testing continues to be debated and effective therapies for many clinically relevant pathogens remain limited. Pulmonary infections are a priority for research efforts in this immunocompromised population.